Characteristic, Levels of lead in the blood, and hypertension of Workers Batteries Home Industry at Talun Village Sukodadi District Lamongan Regency - Lian Dwi Fibrianti; R. Azizah (Universitas Airlangga, 2015)
Abstract: Lead (Pb) is one of the pollutants that can cause hypertension. The objectives of this study were to analyze characteristic, levels of Lead (Pb) in blood and hypertension at home industry workers batteries. This research was an observational descriptive studies and used cross-sectional approach. Data obtained from interviews, questionnaires, and observation. Measurement of blood lead used Atomic Absorption Spectrophotometer and blood pressure measurements used a tensimeter. Samples were selected by total population of 10 workers batteries home industry. The results of the research that most workers age is less than 30 years was 50%, the worker men was 60%, workers who have a habit of smoke was 30%, Pb levels in the blood of workers 30% above the standards set by ATSDR (1999) < 10 Î¼g/dL, and 40% of workers have hypertension. Cross-tabulation showed that workers who have hypertension that workers aged 31–40 years (50%), workers with employment â‰¤ 5 year period (40%), male workers (66.7%), workers who was smoke (100%), workers with no history of hypertension and diabetes (40%) and workers who have levels of lead (Pb) in the blood > 10 Î¼g/dL (100%). Advise the workers to reduce cigarette consumption and wear personal protective equipment such as masks, gloves and boots while they work to reduce exposure of lead (Pb).Keywords: characteristic of workers, levels of lead (Pb) in the blood, hypertension, workers home industry batteries